Esophageal Perforation following Accidental Ingestion of a Razor Blade - Suraj Shrestha; Ranjan Sapkota; Suraj Bhatta; Sanjeev Kharel; Bibek Man Shrestha; Aakriti Sharma (Case Reports in Surgery)
Background. Ingestion of sharp foreign bodies is uncommon and often underreported. It can present with esophageal perforation which is a life-threatening complication requiring prompt diagnosis and management. Case Presentation. We report a case of accidental ingestion of a razor blade in a chronic alcoholic who presented with hematemesis after an esophageal perforation, the diagnosis of which was confirmed by radiology. Conclusion. Early recognition of esophageal perforation is crucial for early intervention. Proper history taking and radiological investigations are a key to reaching a diagnosis.